Astragaloside IV Attenuates Podocyte Apoptosis Mediated by Endoplasmic Reticulum Stress through Upregulating Sarco/Endoplasmic Reticulum Ca2+-ATPase 2 Expression in Diabetic Nephropathy - Guo, Hengjiang; Cao, Aili; Chu, Shuang; Wang, Yi; Zang, Yingjun; Mao, Xiaodong; Wang, Hao; Wang, Yunman; Liu, Cheng; Zhang, Xuemei; Peng, Wen (Frontiers in Pharmacology, 2016)
Sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA) plays a central role in the pathogenesis of diabetes. This protein has been recognized as a potential target for diabetic therapy. In this study, we identified astragaloside IV (AS-IV) as a potent modulator of SERCA inhibiting renal injury in diabetic status. Increasing doses of AS-IV (2, 6 and 18 mg·kg-1·day-1) were administered intragastrically to db/db mice for 8 weeks. Biochemical and histopathological approaches were conducted to evaluate the therapeutic effects of AS-IV. Cultured mouse podocytes were used to further explore the underlying mechanism in vitro. AS-IV dose-dependently increased SERCA activity and SERCA2 expression, and suppressed ER stress-mediated and mitochondria-mediated apoptosis in db/db mouse kidney. AS-IV also normalized glucose tolerance and insulin sensitivity, improved renal function, and ameliorated glomerulosclerosis and renal inflammation in db/db mice. In palmitate stimulated podocytes, AS-IV markedly improved inhibitions of SERCA activity and SERCA2 expression, restored intracellular Ca2+ homeostasis, and attenuated podocyte apoptosis in a dose-dependent manner with a concomitant abrogation of ER stress as evidenced by the downregulation of GRP78, cleaved ATF6, phospho-IRE1α and phospho-PERK, and the inactivation of both ER stress-mediated and mitochondria-mediated apoptotic pathways. Furthermore, SERCA2b knockdown eliminated the effect of AS-IV on ER stress and ER stress-mediated apoptotic pathway, whereas its overexpression exhibited an anti-apoptotic effect. Our data obtained from in vivo and in vitro studies demonstrate that AS-IV attenuates renal injury in diabetes subsequent to inhibiting ER stress-induced podocyte apoptosis through restoring SERCA activity and SERCA2 expression.